Historical Relations between Kazakhstan and Hungary and Their Impact on Economic Cooperation and Development. New Experiences and Perspectives upon Tourism - DULATBEKOV, Nurlan (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
In the context of developing our partnership with the European Union, it is also important to study the prospects for cooperation with individual European countries. Hungary is of great interest in this regard, as a country that has deep historical roots with our people, a country that has passed the path of political and economic reforms and has recently become a member of the EU and NATO. Prospects for the development of cultural and humanitarian relations are becoming wider every year. This fact is facilitated by the historical proximity of the two peoples, and their desire for the revival of national culture and traditions. It is noteworthy that in addition to economic, scientific and cultural cooperation, a productive exchange of experience in the field of public administration, as well as the development of tourism, has been established between Kazakhstan and Hungary.